ANALISIS ARTIKEL PERAN PELATIHAN DAN PENGEMBANGAN DALAM MENINGKATKAN KOMPETENSI KARYAWAN - Haratua, Chandra Sagul; Sugian, Ugi; L, Riani Siti Diah; Kohar, Abdul; Saefullah, Saefullah (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
Amid global competition and rapid organizational change, enhancing employee competence has become a crucial factor for organizational sustainability. This article explores the strategic role of training and development in improving employee competencies through a literature review of national and international sources published over the last ten years. The findings indicate that well-planned training and continuous career development programs can enhance technical skills, work attitudes, motivation, and employee loyalty. Furthermore, career development that aligns with individual needs plays a significant role in preparing employees to face future job challenges. Human resource management holds a vital role in designing training programs that align with both organizational goals and employee growth. The success of such programs is also influenced by managerial support, a learning-oriented organizational culture, and the effective use of technology. With the right approach and long-term orientation, training and development not only positively impact individual performance but also contribute to improving overall organizational effectiveness and competitiveness. ABSTRAKDi tengah kompetisi global dan perubahan organisasi yang cepat, penguatan kompetensi karyawan menjadi aspek krusial bagi keberlangsungan organisasi. Artikel ini membahas peran strategis pelatihan dan pengembangan dalam meningkatkan kompetensi karyawan melalui kajian literatur selama sepuluh tahun terakhir dari berbagai sumber nasional dan internasional. Temuan menunjukkan bahwa pelatihan yang terencana serta program pengembangan karier yang berkesinambungan mampu meningkatkan kemampuan teknis, sikap kerja, motivasi, dan loyalitas karyawan. Selain itu, pengembangan karier yang sesuai dengan kebutuhan individu juga berperan dalam mempersiapkan karyawan menghadapi tantangan pekerjaan masa depan. Peran manajemen sumber daya manusia menjadi sangat penting dalam merancang program pelatihan yang selaras dengan kebutuhan organisasi dan perkembangan karyawan. Keberhasilan program ini turut ditentukan oleh dukungan manajerial, budaya organisasi yang mendukung pembelajaran, serta pemanfaatan teknologi. Dengan pendekatan yang tepat dan berorientasi jangka panjang, pelatihan dan pengembangan tidak hanya memberi dampak positif pada individu, tetapi juga berkontribusi dalam meningkatkan kinerja dan daya saing organisasi secara keseluruhan.